Digital transformation of Islamic education through deep learning in the postmodern era - Bahijah, Ijah; Khumairoh, Salma Aufie (Journal of Professional Teacher Education, 2025)
This study aims to examine the digital transformation of Islamic education through the application of deep learning technology in the postmodern era. The research method used a literature review guided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Articles were searched for using Google Scholar with specific keywords, yielding 95 initial articles. After the selection process (removal of duplicates, screening of titles and abstracts, and full-text assessment), only 5 articles met the inclusion criteria. Content analysis was conducted descriptively to identify the main themes. The results of the study found three important themes: (1) the integration of technology in Islamic education management, (2) the application of deep learning in Islamic learning, and (3) adaptive leadership in digital Islamic education. These findings confirm that deep learning can support personalized learning, strengthen education management, and encourage adaptive visionary leadership.  However, this study also found limitations such as low digital literacy among educators and uneven infrastructure. The study concluded that deep learning-based digital transformation is not only a technological innovation but also a strategic step to maintain the relevance of Islamic values amid the progress of the times. Further research is recommended to expand the database, increase the number of literature analyzed, and test this conceptual model in an empirical context.